2011
DOI: 10.4061/2011/816897
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor Inhibitor-Induced Hypertension: Basics for Primary Care Providers

Abstract: Frequently, primary care providers continue to manage the overall medical care of cancer patients. With newer and often more potent antitumor agents, patients may present to their local physicians with drug-induced toxicities such as hypertension induced by vascular endothelial growth factor (VEGF) inhibitors. It is imperative that these healthcare providers are aware of basic aspects of this drug class, as its use has increased significantly in the last several years. Uncontrolled or malignant hypertension d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 34 publications
1
35
0
Order By: Relevance
“…5,10 Frequencies of hypertension for other VEGFR TKIs vary from 1% to 40%. 16,17 Hypertension has been shown to be associated with improved clinical outcome in patients with renal cell carcinoma treated with VEGFR TKIs and probably, therefore, indicates on-target biological activity rather than a side effect. 18,19 Serum tivozanib levels in this combination study were comparable with those observed in single-agent studies.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…5,10 Frequencies of hypertension for other VEGFR TKIs vary from 1% to 40%. 16,17 Hypertension has been shown to be associated with improved clinical outcome in patients with renal cell carcinoma treated with VEGFR TKIs and probably, therefore, indicates on-target biological activity rather than a side effect. 18,19 Serum tivozanib levels in this combination study were comparable with those observed in single-agent studies.…”
Section: Discussionmentioning
confidence: 98%
“…16,17 Hypertension developed in 53% of patients, was easily manageable, and only 2 patients required dose reduction. Hypertension did not result in interruption or termination of treatment in this study.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF is expressed in virtually every tissue and is required for development-related angiogenesis and adult vascular homeostasis [26]. VEGF signaling is closely correlated with hypertension and use of VEGF inhibitors in cancer treatment causes pathological hypertension, probably due to decreased number of small arteries and increased arterial stiffness in proximal or distal vessels [27]. Transforming growth factor β1 (TGF-β1) is a multifunctional peptide produced by many cell types and affecting angiogenesis, immune regulations, and wound healing [28].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials and observational studies have also reported an increased incidence of hypertension during systemic, but not intra-ocular, treatment with all commercially available anti-VEGF drugs [3]. Differences in patient characteristics, type of cancer, anti-VEGF treatment regimens and methods for assessing blood pressure notwithstanding, the reported incidence of hypertension ranges between 9% and 67%, and the incidence of severe hypertension (Grade 3 or Grade 4) ranges between 3% and 18% [9]. The available evidence suggests that both the incidence and the severity of anti-VEGF-induced hypertension are dosedependent [10].…”
Section: Anti-vegf-induced Hypertension and Cancer Outcomes: Translatmentioning
confidence: 94%